Olfactory Response of an Assassin Bug, Rhynocoris Longifrons (Insecta: Hemiptera: Reduviidae) To the Hexane Extracts of Different Agricultural Insect Pests - Kumar, A Ganesh; Ambrose, Dunston P (International Research Journal of Insect Sciences, 2014)
The predator-prey interaction of five prey species with the assassin bug, Rhynocoris longifrons (Stål) (Hemiptera: Reduviidae) was assessed in a Y-shaped olfactometer and the prey preference was assessed in six-arm olfactometer provided with the bodyextracts in hexane. Although R. longifrons responded to all the hexane extracts of testedinsect pests, R. longifrons showed maximum response to the lepidopterans Spodoptera litura (F.) (6.67±1.18 min), Helicoverpa armigera (Hübner) (5.17±0.89 min) and Achaea janata (L.) (4.42±1.04 min) followed by the coleopteran Mylabris indica (Thunberg) (3.00±0.82 min) and the least response to the hemipteran Dysdercus cingulatus (F.) (2.42±0.76 min).Thus, the present study clearly reveals the order of the host preference of R. longifrons to the tested hexane extracts of the taxonomically diverse insect pests.